The usage of Bupivacaina as anesthetic agent in knee arthroscopy. - José Julio Ojeda González; Evangelina Dávila Cabo de Villa; Ana María Machado Consuegra; José Toledo Torres; Carlos M. Hernández (Centro Provincial de Información de Ciencias Médicas. Cienfuegos, 2003)
Introduction: Artroscopy of the knee is a procedure that is frequently developed as a diagnostic and therapeutic means in patients who suffer among other diseases, from chronic sinuvitis, lesions of the meniscus and adherence . A great number of these patients receive medical assistance at the outpatient department of the orthopaedic department where the need of its use is assessed. It is a relatively short procedure that has few risks when it is performed with the appropriate technique. Objective: To show the use of intra articular Bupivacaine 0,25 % in the artroscopy of the knee. Method: Retrospective study carried out at the University Hospital ¨Dr. Gustavo Aldereguía Lima¨ from Cienfuegos province from September 2002 to February 2003. This study was developed with 20 patients who were initially assisted at the service of Orthopaedics in which a group of therapeutic procedures were decided. Bupivacaine 0,25 % together with Epinephrine 0,1 % in a dose of 0,1 ml were injected in the intra articular space in a volume of 20 ml distributed in 4 sections with 5 ml each. At the level of the section where the artroscope was inserted , 5 ml of Bupivacaine 0,25 % was applied. Result: the age of the patient ranged 30 to 61 years of age with a media of 44,6 years and a standard deviation of 12,6 years. The introduction and application of the procedure throughout artroscopy was possible in al patients. Conclusion: Bupivacaine is a good local anaesthetic because of its slow action since the onset of application and its prolonged duration, and because of the intensity and the duration of the sensorial block that is superior to the motor block.